PENGARUH PERSEPSI HARGA DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG DI RESTORAN HAKATA IKKOUSHA MEDAN - Sofian, Abu; Sarumaha, Imelda Santi; Purba, Kuras (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
The purpose of this study is to ascertain how the perception of price and service quality affects patrons' desire to repurchase from Hakata Ikkousha Medan. Partially and concurrently, the impact of pricing perception and service quality on repurchase interest will be examined. This study used a quantitative method and was a survey. The patrons of the restaurant Hakata Ikkousha Medan made up the research population. The incidental sampling technique was used to choose the sample, which included 94 customers. The study's findings show that the repurchase interest variable (Y) is significantly positively impacted by the service quality variable (X1) and the price perception variable (X2) is considerably positively impacted by the repurchase interest variable.